Clinical significance of TAM receptor in the minor salivary glands of patients with Sjögren’s disease - Sung-Eun Choi; Ji-Hyoun Kang; Dong-Jin Park; Nah Ihm Kim; Ji Shin Lee; Kyung Chul Yoon; Shin-Seok Lee (Scientific Reports)
Abstract Sjögren’s disease is a chronic autoimmune disorder characterized by lymphocytic infiltration of the salivary and lacrimal glands, often accompanied by systemic manifestations. Dysregulation of immune homeostasis, including impaired clearance of apoptotic cells and aberrant type I interferon (IFN) signaling, plays a key role in its pathogenesis. Tyro3, Axl, and Mer tyrosine kinase (MerTK)—collectively known as TAM receptors—regulate efferocytosis and dampen IFN-mediated inflammation. While deficiencies in TAM signaling have been implicated in various autoimmune diseases, their role in Sjögren’s disease remains poorly understood. We evaluated the expression of Tyro3, Axl, and MerTK in minor salivary gland tissues from 74 patients with Sjögren’s disease using immunohistochemistry. Associations with clinical and laboratory features, including the EULAR Sjögren’s Syndrome Disease Activity Index (ESSDAI) and Damage Index (SSDDI), were analyzed. Among the TAM receptors, MerTK expression was significantly associated with higher focus scores, serum IgG levels, anti-SS-A antibody titers, and increased ESSDAI and SSDDI scores. Tyro3 and Axl expression did not show meaningful correlations with clinical parameters. In conclusion, MerTK expression in minor salivary glands is associated with increased disease activity and immune activation in Sjögren’s disease, suggesting its potential role as a tissue biomarker and a modulator of local immune responses.